2002
DOI: 10.1542/peds.109.2.e23
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Childhood Height to Obesity Among Adults: The Bogalusa Heart Study

Abstract: ABSTRACT.Objective. In a previous study of the role of various predictors of adult obesity, we found that relatively tall children had a higher body mass index (BMI; kg/m 2 ) in early adulthood. In this study, the objective was to determine whether childhood height is related to adult adiposity and whether the association is independent of childhood levels of BMI and triceps skinfold thickness.Methods. The longitudinal relations of childhood height to relative weight and skinfold (sum of subscapular and tricep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
1
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 30 publications
6
34
1
6
Order By: Relevance
“…24 Height at these ages did not predict BMI at age 17 years in either the stunted or non-stunted Jamaican groups in this study. Height at 11 years was associated with later BMI, but this was owing to the correlation between height and BMI at 11 years.…”
Section: Discussioncontrasting
confidence: 67%
“…24 Height at these ages did not predict BMI at age 17 years in either the stunted or non-stunted Jamaican groups in this study. Height at 11 years was associated with later BMI, but this was owing to the correlation between height and BMI at 11 years.…”
Section: Discussioncontrasting
confidence: 67%
“…We also report a positive association of height with body fatness in children that has been observed in preschool (Buchan et al, 2007) and school age children (Freedman et al, 2004) previously. Increased height-for-age in childhood is a predictor of adult obesity (Freedman et al, 2002). BMI is a measure of total mass in relation to height but we show by ethnic group and also for individuals that FM and FFM vary for the same height and weight.…”
Section: Discussionmentioning
confidence: 52%
“…Research in adult obesity has shown that BMI values in adulthood were related to BMI patterns before 6 years of age, and rapid weight gain in the first years of life was associated with adult obesity [6,8,11,14]. A previous study has also shown that both greater BMI and weight gain starting from 2 or 3 years of age were associated with adult adiposity and central obesity [16].…”
Section: Discussionmentioning
confidence: 97%